2015
DOI: 10.1016/j.str.2014.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Unique Structural Features in DNA Polymerase IV Enable Efficient Bypass of the N 2 Adduct Induced by the Nitrofurazone Antibiotic

Abstract: The reduction in the efficacy of therapeutic antibiotics represents a global problem of increasing intensity and concern. Nitrofuran antibiotics act primarily through the formation of covalent adducts at the N(2) atom of the deoxyguanosine nucleotide in genomic DNA. These adducts inhibit replicative DNA polymerases (dPols), leading to the death of the prokaryote. N(2)-furfuryl-deoxyguanosine (fdG) represents a stable structural analog of the nitrofuran-induced adducts. Unlike other known dPols, DNA polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 74 publications
6
53
0
Order By: Relevance
“…Only rather subtle dNTP‐induced conformational changes in Y‐family DNA Pols have been observed. Indeed, the difference in rmsd in the crystal structures of DinB ternary complexes with a correct or an incorrect incoming nucleotide is 0.35–0.43 Å , which is similar (0.4 Å) to what is found in ternary complex structures of DinB bound to undamaged DNA or DNA containing N 2 fG . Dpo4 undergoes an apparent movement of domains upon binding to DNA, but very little or no change in fluorescence resonance energy transfer efficiency is observed upon formation of a ternary complex .…”
Section: Introductionsupporting
confidence: 67%
“…Only rather subtle dNTP‐induced conformational changes in Y‐family DNA Pols have been observed. Indeed, the difference in rmsd in the crystal structures of DinB ternary complexes with a correct or an incorrect incoming nucleotide is 0.35–0.43 Å , which is similar (0.4 Å) to what is found in ternary complex structures of DinB bound to undamaged DNA or DNA containing N 2 fG . Dpo4 undergoes an apparent movement of domains upon binding to DNA, but very little or no change in fluorescence resonance energy transfer efficiency is observed upon formation of a ternary complex .…”
Section: Introductionsupporting
confidence: 67%
“…Foti and colleagues showed that incorporation of the oxidized nucleotide poolespecially 8oxodGTP (8odGTP)-into the genome by PolIV contributes substantially to the deleterious effects of ROS on cellular physiology. [7] PolIV has significant ability to incorporate 8odGTP opposite dA but not dC,e ven at high concentrations of 8odGTP ( Figure 1). [5b,6] The8 odGTP incorporation activity of PolIV is in addition to previously observed roles in stress-induced mutagenesis or translesion synthesis that aid survival of the cell.…”
Section: Jithesh Kottur and Deepak T Nair*mentioning
confidence: 99%
“…Using hydroxylamine mutagenesis, we identified variants of E. coli UmuC (Fig. 1) that conferred resistance to nitrofurazone (NFZ), which is thought to cause the N 2 -furfuryl-dG lesion, considered a cognate lesion of DinB [41,43] but a non-cognate lesion of UmuC (Fig. 1).…”
Section: Genetic Transductionmentioning
confidence: 99%
“…whereas UmuC variants H282P and T412I do not N 2 -furfuryl-dG is thought to be the lesion resulting from treatment with NFZ and is considered to be a cognate lesion of DinB [41][42][43]. Agents that form N 2 -dG adducts can also form N 6 -dA adducts.…”
Section: Umuc Variant A9v Weakly Bypasses N 2 -Furfuryl-dg In Vitromentioning
confidence: 99%
See 1 more Smart Citation